Medien, Macht, Medienmacht: Wolfgang Koeppens Das Treibhaus (1953) und Heinrich Bölls Die verlorene Ehre der Katharina Blum (1974) - van Laak, Lothar (Literatur und Politik. Zwischen Engagement und „Neuer Subjektivität“)

Einbildungskraft und Intermedialität bei Friedrich von Spee und Catharina Regina von Greiffenberg - van Laak, Lothar (Intermedialität in der Frühen Neuzeit. Formen - Funktionen - Konzepte)

Schulisches Wohlbefinden als Qualitätsmerkmal inklusiver Schulen ‒ Unterrichtsentwicklung im Rahmen eines Lehrer-Forscher-Projekts an der Laborschule Bielefeld - Külker, Anna; Dorniak, Marlena; Geist, Sabine; Kullmann, Harry; Lutter, Natascha; Lütje-Klose, Birgit; Siepmann, Christof ({Leistung inklusive? Inklusion in der Leistungsgesellschaft. Band II: Unterricht, Leistungsbewertung und Schulentwicklung})

Spielarten des Dialoggedichts in der deutschsprachigen Galanterie - Elit, Stefan (Dialoggedicht / Dialogue Poem. Studien zur deutschen, englischen und romanischen Lyrik / Studies in German, English and Romance Language Poetry (Germanisch-Romanische Monatsschrift. Beiheft 84))

Fortpflanzungsnöte der Gegenwart in John von Düffels Roman "Beste Jahre" - Elit, Stefan (Arbeitsbuch John von Düffel. Stimmen geben – Stimmen erzählen (Literarisches Leben heute 6))

Rüdiger Scholz: Max von der Grün. Politischer Schriftsteller und Humanist. Mit einer Würdigung von Werner Bräunigs "Rummelplatz", Würzburg 2015 - Elit, Stefan (Germanistik 57, H. 3-4, Nr. 6140)

Das Bild der DDR in Literatur, Film und Internet. 25 Jahre Erinnerung und Deutung, hg. v. Hans-Joachim Veen, Red. Manuel Leppert, Köln u.a. 2015 - Elit, Stefan (Germanistik 57, H. 3-4, Nr. 6491)

Sylvia Fischer: Dass Hämmer und Herzen synchron erschallen. Erkundungen zu Heimat in Literatur und Film der DDR der 50er und 60er Jahre, Oxford u.a. 2015 (German life and civilization 60) - Elit, Stefan (Germanistik 58, H. 1-2, Nr. 3094)

„Gabe, Tausch und êre in der Alexiuslegende“ - Egidi, Margreth (Anerkennung und die Möglichkeiten der Gabe. Literaturwissenschaftliche Beiträge, unter Mitarbeit von Malena Ratzke und Britta Wittchen (Hamburger Beiträge zur Germanistik 58))

„Die Figur des Liebenden – Aporien der Kommunikation im mittelhochdeutschen Minnesang“ - Egidi, Margreth (Im Gewand der Tugend: Grenzfiguren der Aufrichtigkeit)

Was bringen Schülerinnen und Schüler am Übergang von der Erst- in die Anschlussförderung mit? Eine Handreichung von Lehrerinnen und Lehrern für Lehrerinnen und Lehrer - Frenzel, Beate; Günther, Katrin; Knauff, Michaele; Lüttgens, Philipp; Runskat, Tanja

Intro Deutsch als Zweitsprache. Kursbuch zur Vorbereitung auf den Regelunterricht der Sekundarstufe. Hrsg.: Gabriele Kniffka, Birgit Neuer - Altun, Tülay; Bollmann, Laura; Borowski, Damaris; Eberhart, Sieglinde; Frenzel, Beate; Gretsch, Petra; Günther, Katrin; Harren, Inga; Hinderer, Marcel; Kniffka, Gabriele; Mavruk, Gülsah; Neuer, Birgi; et al.

DaZ für den Fachunterricht der Sekundarstufe I. Gesellschaftswissenschaften Klasse 5-10. Materialien, Tipps, Hilfen und Methoden.

Measuring and modeling salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
For almost three decades, the theory of visual attention (TVA) has been successful in mathematically describing and explaining a wide variety of phenomena in visual selection and recognition with high quantitative precision. Interestingly, the influence of feature contrast on attention has been included in TVA only recently, although it has been extensively studied outside the TVA framework. The present approach further develops this extension of TVA’s scope by measuring and modeling salience. An empirical measure of salience is achieved by linking different (orientation and luminance) contrasts to a TVA parameter. In the modeling part, the function relating feature contrasts to salience is described mathematically and tested against alternatives by Bayesian model comparison. This model comparison reveals that the power function is an appropriate model of salience growth in the dimensions of orientation and luminance contrast. Furthermore, if contrasts from the two dimensions are comb
Keywords: Salience; Visual attention; Bayesian inference; Theory of visual attention; Computational modeling; Inference; Object Recognition; Theories; Visual Perception; Visual Attention; Luminance; Perceptual Orientation; Statistical Probability; Stimulus Salience; Computational Modeling

Measuring Attention and Visual Processing Speed by Model-based Analysis of Temporal-order Judgments - Tünnermann, Jan; Krüger, Alexander; Scharlau, Ingrid (Journal of Visualized Experiments)
This protocol describes how to conduct temporal-order experiments to measure visual processing speed and the attentional resource distribution. The proposed method is based on a new and synergistic combination of three components: the temporal-order judgments (TOJ) paradigm, Bundesen's Theory of Visual Attention (TVA), and a hierarchical Bayesian estimation framework. The method provides readily interpretable parameters, which are supported by the theoretical and neurophysiological underpinnings of TVA. Using TOJs, TVA-based estimates can be obtained for a broad range of stimuli, whereas traditional paradigms used with TVA are mainly limited to letters and digits. Finally, the meaningful parameters of the proposed model allow for the establishment of a hierarchical Bayesian model. Such a statistical model allows assessing results in one coherent analysis both on the subject and the group level. To demonstrate the feasibility and versatility of this new approach, three experiments are reported with attention manipulations in synthetic pop-out displays, natural images, and a cued letter-report paradigm.

Gegen das weibliche Cooling-out in der Wissenschaft. Mentoring für Frauen in der Promotionsphase - Steinhausen, Julia; Scharlau, Ingrid (Praxishandbuch Mentoring in der Wissenschaft)

Diese Linie sollte man verlängern: Zum Verhältnis der Hochschuldidaktik zu den Fächern - Scharlau, Ingrid (Zwischen Wissenschaftsforschung, Wissenschaftspropädeutik und Hochschulpolitik. Hochschuldidaktik als lebendige Werkstatt. Festschrift für Ludwig Huber zum 80. Geburtstag)

The interplay between subjective abilities and subjective demands and its relationship with academic success. An application of the person–environment fit theory - Bohndick, Carla; Rosman, Tom; Kohlmeyer, Susanne; Buhl, Heike M. (Higher Education)
In this study, we draw on person–environment fit theory to analyze whether academic success is best explained by individual abilities subjectively exceeding situational demands or by abilities matching the demands. Moreover, we disentangled effects of perceived abilities and subjective person–environment (P-E) fit on academic success. All in all, 693 teacher education students participated in an online questionnaire. Students were asked to rate general requirements of their academic programs (e.g., self-discipline) on a 5-point scale in terms of (1) their own abilities and (2) the perceived relevance for their studies. P-E fit was determined by difference scores between abilities and relevance ratings. Academic success was assessed by grades, perceived performance, and study satisfaction. Data were analyzed through structural equation modeling and suggest that academic success is best explained by a match between abilities and demands. Moreover, all three criteria for academic success were more strongly related to subjective fit than to subjective abilities.
Keywords: Academic success; Person–environment fit theory; Demands–abilities fit; Higher education

Competencies and career choice motives: characteristics of high school students interested in teacher education programmes - Bohndick, Carla; Kohlmeyer, Susanne; Buhl, Heike M. (Journal of Education for Teaching)
In contrast to other career choices, the teaching profession seems familiar to those interested in teaching because they have had the chance to observe teachers for years. This phenomenon is known as the apprenticeship of observation and manifests in naïve ideas and expectations of teaching among teacher students. Therefore, characteristics of students interested in becoming teachers are important for early teacher education and counselling. These characteristics include competencies and motives, but nothing is known about their relationship to each other. Following international teaching standards and the expectancy-value framework, this paper analyses associations between both. Three competencies (i.e. planning, communication and cooperation) and seven career choice motives were examined using a paper–pencil survey of 907 high school students. Altogether, 463 students were able to imagine becoming a teacher and were included in the analyses. SEM analyses showed that (1) of all the competencies, communication had the most associations with motives, (2) the motive ‘low difficulty of study’ is positively related to planning, (3) the findings regarding extrinsic motives are ambiguous, and (4) gender differences are marginal. Practical implications for early teacher education and counselling are discussed.
Keywords: Education

Bildung und Lesesozialisation im Elternhaus - Buhl, Heike M.; Hilkenmeier, Johanna (Handbuch Entwicklungs- und Erziehungspsychologie)
Deutliche Unterschiede im Bildungserfolg von Kindern abhängig vom familialen Hintergrund zeigen, dass, ungeachtet der schulischen Bemühungen um die kindliche Bildung, die Familie weiterhin ein wesentlicher Einflussfaktor ist. Vor diesem Hintergrund werden im Folgenden die Wege erörtert, über die sich diese Einflüsse realisieren. Nach einem Überblick zu einschlägigen Prozessen werden in diesem Beitrag familiale Wirkungszusammenhänge am Beispiel der Lesesozialisation genauer beleuchtet. Vor diesem Hintergrund werden abschließend Programme zur Förderung der familialen Unterstützung diskutiert.
Keywords: Lesesozialisation; Familiale Erziehung; Familienklima; Kindliche Bildung; Bildungserwartungen; Häusliche Anregung; Home literacy environment; Vorlesen; Literacy